Making Concepts the Application Towards Consumer Behavior Through Bali Tourism as A Stimulation After Pandemic to Improve the Economy of Local Population - Dwi Vita Raudatul Jannah; Marceila Zahra Nindita Pramesti; Sahira Dwi Cahyani Syam (UPT Penerbitan Universitas Jember, 2021)
Because of Covid-19, Indonesia has declared a state of emergency on its main island of Java, as well as the tourist hotspot of Bali. President Joko Widodo's gave the statement comes as the country grapples with repeated outbreaks and an alarming increase of COVID-19 cases. The Balinese government has implemented an extremely severe health protocol system in response to this situation, particularly the requirements for visiting Bali. Fortunately, this rule produces significant results; at the end of 2020, Bali announced that at least three areas of the island are ready to accept tourists again; this is what inspired us to develop a service concept innovation with a health protocol system and destination promotion through features in the app, so visitors do not have to be concerned about their safety in this unstable situation. This program is also in line with President Joko Widodo's directive that tourism must constantly adapt to technological and market demands. With qualitative approaches, research is conducted in natural settings to interpret observed occurrences and is carried out through logical analysis. A critical analytical method is required as a contribution to the phenomena that occur. Keywords: Application, Bali Tourism, Economic Activity, Pandemic.